Exploring the Development of Community Parks in Urban–Rural Fringe Areas in China: Expert and Policy Perspectives on Sustainable Design and Strategy Planning - Ke Wang; Ian Mell; Jeremy Carter (Land)
Rapid urban expansion has led to an increasing number of people relocating to Urban–Rural Fringe Areas (URFAs) in China, with related development placing pressure on ecosystems in these locations. Community parks (CPs) are a key category of urban public park (UPPs) in Chinese planning and play a vital role in improving residents’ quality of life and enhancing regional environment, whilst also promoting sustainable urban development. Consequently, CPs are considered by many to be integral components of “communities” in Chinese cities. Drawing on documentary analysis and field research, this paper explores the socio-economic and ecological values associated with CP investments in URFAs in China. It assesses governmental policies and expert perspectives concerning CPs’ development in URFAs and analyses the factors influencing their planning and delivery. The research highlights how policy and stakeholders’ viewpoints impact the development of sustainable green space in URFAs. To enhance the construction of multi-functional CPs in URFAs, we propose a series of characteristics that need to be considered in future developments, including stakeholder engagement, resident needs, and park design. These insights offer an evidence-based reference for decision-makers, aiming to better meet the requirements of residents and support the development of urban sustainability.